2016
DOI: 10.3390/risks4040048
|View full text |Cite
|
Sign up to set email alerts
|

How Does Reinsurance Create Value to an Insurer? A Cost-Benefit Analysis Incorporating Default Risk

Abstract: Abstract:Reinsurance is often empirically hailed as a value-adding risk management strategy which an insurer can utilize to achieve various business objectives.In the context of a distortion-risk-measure-based three-party model incorporating a policyholder, insurer and reinsurer, this article formulates explicitly the optimal insurance-reinsurance strategies from the perspective of the insurer. Our analytic solutions are complemented by intuitive but scientifically rigorous explanations on the marginal cost an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…Other downsides of excessive usage of reinsurance and low income retention include counter increased counter party risk (Lo, 2016). This is due to the fact that reinsurers do not have a contractual relationship with the insured and in case they do not pay the share of a claim to the insurance firm, the latter will be completely liable to the insured.…”
Section: Nyandwi Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Other downsides of excessive usage of reinsurance and low income retention include counter increased counter party risk (Lo, 2016). This is due to the fact that reinsurers do not have a contractual relationship with the insured and in case they do not pay the share of a claim to the insurance firm, the latter will be completely liable to the insured.…”
Section: Nyandwi Et Almentioning
confidence: 99%
“…The cost of reinsurance for Kenyan general insurers averaged 28.37% with a retention ratio of 71.63% for the period of study from 2015 to 2019 (IRA, 2020 2020),the average income retention for the same period from 2015 to 2019 was 55.25% for Uganda, 49.92% for Tanzania and 65.10% for Burundi. Furthermore, studies also indicated other risks associated with overreliance on reinsurance such as credit and liquidity risk (Lo, 2016) and insolvency risk which may force insurers to inject more capital (Mao et al, 2015;Caporale et al, 2017).…”
Section: Problem Statementmentioning
confidence: 99%